2023
DOI: 10.1097/shk.0000000000002118
|View full text |Cite
|
Sign up to set email alerts
|

PROPHYLACTIC nCMT-3 ATTENUATES SEPSIS-INDUCED ACUTE KIDNEY INJURY IN ASSOCIATION WITH NLRP3 INFLAMMASOME ACTIVATION AND APOPTOSIS

Abstract: Background: The kidney is the most common extrapulmonary organ injured in sepsis. The current study examines the ability of aerosolized nanochemically modified tetracycline 3 (nCMT-3), a pleiotropic anti-inflammatory agent, to attenuate acute kidney injury (AKI) caused by intratracheal LPS. Methods: C57BL/6 mice received aerosolized intratracheal nCMT-3 (1 mg/kg) or saline, followed by intratracheal LPS (2.5 mg/kg) to induce acute lung injury–induced AKI. Tissues were harvested at 24 h. The effects of nCMT-3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Given its acute onset and complex pathophysiology involving multiple cellular pathways and processes, it has posed a significant challenge for physicians (1)(2)(3)(4)(36)(37)(38). However, because of recent advances in elucidating the pathways involving inflammation, innate immunity and DAMPs, promising progress has been made in attenuating the initial injury (8,39,40). One such DAMP is eCIRP, which was initially discovered to be elevated in the circulation of critical care patients during hemorrhagic shock or septic shock (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given its acute onset and complex pathophysiology involving multiple cellular pathways and processes, it has posed a significant challenge for physicians (1)(2)(3)(4)(36)(37)(38). However, because of recent advances in elucidating the pathways involving inflammation, innate immunity and DAMPs, promising progress has been made in attenuating the initial injury (8,39,40). One such DAMP is eCIRP, which was initially discovered to be elevated in the circulation of critical care patients during hemorrhagic shock or septic shock (16).…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion exacerbates the initial injury by triggering an inflammatory response and via generation of reactive oxygen species, causing further damage in a compromised environment (5)(6)(7)(8). Regarding renal I/R injury, tubular epithelial tissue in the kidneys is severely affected, releasing cytokines and damage-associated molecular patterns (DAMPs), which engage the innate immune system and cause additional injury (5,(8)(9)(10)(11)(12). Understanding the molecular pathways in AKI pathogenesis and inflammation helps identify potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis was a disease that causes inflammation throughout the body and could lead to shock or death in severe cases, and AKI was the most common organ dysfunction caused by sepsis (5,29,30). Although more and more researchers were focusing on sepsis, its complex pathogenesis made the treatment of sepsis still difficult (31)(32)(33). Most of the current studies on AKI had been explored on the basis of AKI cell models constructed by LPS-induced cell damage (28,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complicated pathogenesis of AKI caused by sepsis, the exploration of potentially effective treatment options becomes particularly important. Studies have shown that intratracheal atomization of tetracycline 3 (nCMT-3) with nanochemical modification in 57BL/6 mice alleviated LPS-induced AKI by inhibiting renal NLRP3 inflammasome activation, renal inflammation, and cell apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%